Hubungan Lingkungan Fisik Ruang Tidur dan Keluarga dengan Kasus Baru Tuberkulosis Paru BTA Positif di Wilayah Kerja Puskesmas Songgon Banyuwangi - Ismiyanti, Ayudita; Prasasti, Corie Indria; Astutik, Erni (Window of Health : Jurnal Kesehatan, 2018)
Tuberculosis (TB) is a contagious infectious disease due to the bacterium Mycobacterium tuberculosis. Until now, TB disease is still one of the world's health problems and its existence is often linked to environmental problems. This study aims to analyze the physical environmental factors of the house, especially in the bedroom and familiy room associated with smear positive pulmonary tuberculosis new cases in the work area of ​​Puskesmas Songgon Banyuwangi. The design of this research is case control, with the comparison of case:control is 1: 2. A total of 15 people from the case group were taken from SITT (Integrated Tuberculosis Information System) Puskesmas Songgon Banyuwangi and selected using simple random sampling method, while 30 control group were neighbors of case group matching based on gender. Dependent variables is new cases of smear positive pulmonary tuberculosis in the work area of ​​Puskesmas Songgon Banyuwangi and independent variables include ventilation, temperature, humidity, and lighting in bedroom and famiy room. The result of chi square analysis showed that there was a significant correlation between bedroom lighting (OR=4,667; 95%CI=1,237-17,600; p=0,043) and family room lighting (OR=4,571; 95%CI=1,182-17,678; p=0,039) with a new case of smear positive pulmonary TB in the work area of Puskesmas Songgon Banyuwangi. Therefore, the need for awareness to the community, especially the people with pulmonary tuberculosis, by health personnel Pukesmas Songgon Banyuwangi about the importance of keeping the home environment to stay healthy, one of them by allowing air to change and sunlight can enter the house by opening the window in every room house in the morning, and replace the brick tile with glass tile. Keywords : Pulmonary Tuberculosis, smear, lighting, bedroom, family room